COMPUTATIONAL ANALYSIS OF INTERACTIONS BETWEEN ANTI-EPILEPTIC DRUGS AND IMPORTANT PLACENTAL PROTEINS-A POSSIBLE ROUTE FOR NEURAL TUBE DEFECTS IN HUMANS - Vijayasri, Santhanam; Archana, Hari; Agrawal, Arvind; Hopper, Waheeta (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The reason behind the occurrence of Neural Tube Defects (NTDs) in pregnant women treated with certain Anti-Epileptic Drugs (AEDs) such as Carbamazepine, Valproate, Lamotrigine, Phenobarbital, etc., is not yet known. The relationship between Folic Acid intake and NTDs is not yet established. Folate receptors play a critical role in mediating placental transport of maternal folate to the foetus. Another important protein is Carnitine O-acetyltransferase that is involved in the transport of carnitine, which is much needed for foetal metabolic functions and tissue development. The objective of this study is to understand the interaction of AEDs with two important placental proteins through a docking approach to establishing a suitable explanation of AED's role in NTD. Methods: A generic algorithm based docking was used to identify and study the mode of interactions between the drugs and placental proteins. For comparison purpose, the natural ligands of these receptors have also been included in the dataset containing AEDs. Results: Both bonded and non-bonded interactions were observed between AEDs and the crucial residues of these proteins. The drugs formed complex with these proteins with satisfactory binding energy. Some amount of Electrostatic interaction was also observed among a few pairs of protein residue and drugÂ molecules. Conclusion: We suggest that these drug-protein associations, involving bonded and non-bonded interactions, could be a possible portal by which certain AEDs induce NTDs in the foetus. Higher interaction of Pantothenic Acid with Folate Receptor could be a mechanism through which Pantothenic Acid inhibits Valproic Acid-induced NTDs. And thus, its supplementation can specifically prevent Valproic Acid-induced NTDs. The above mechanism also explains how increased intake of Folic Acid during pregnancy can reduce the occurrence of NTDs. Keywords: Neural Tube Defect, Anti-epileptic drug, Placenta, Folate transporters, Docking, Carnitine O-acetyltransferase